Al-Amanah as a Managerial Catalyst for Microenterprise Development: Evidence from Salsabel Homestay - Syahril Jumadil Awal; Kamiruddin Kamiruddin; Munawarah Munawarah (Universitas Persada Indonesia YAI, 2026)
This study examines the implementation of Al-Amanah as a managerial foundation in the development of Salsabel Homestay, a microenterprise in Bone Regency, Indonesia. Using a qualitative case study approach, data were collected through observation, interviews, and documentation involving the owner, employees, and customers. The findings indicate that Al-Amanah is reflected in leadership, decision-making, responsibility, and customer service practices. Its implementation enhances employee commitment, customer trust, service quality, and business reputation. The study concludes that Al-Amanah functions as both an ethical value and a strategic managerial principle that supports sustainable microenterprise growth and organizational effectiveness.